A modified Continuous Quality Improvement approach to improve culturally and socially inclusive care within rural health services. (23rd March 2018) - Mitchell, Olivia; Malatzky, Christina; Bourke, Lisa; Farmer, Jane
Abstract: Background: The sickest Australians are often those belonging to non‐privileged groups, including Indigenous Australians, gay, lesbian, bisexual, transsexual, intersex and queer people, people from culturally and linguistically diverse backgrounds, socioeconomically disadvantaged groups, and people with disabilities and low English literacy. These consumers are not always engaged by, or included within, mainstream health services, particularly in rural Australia where health services are limited in number and tend to be generalist in nature. Objective: The aim of this study was to present a new approach for improving the sociocultural inclusivity of mainstream, generalist, rural, health care organisations. Design: This approach combines a modified Continuous Quality Improvement framework with Participatory Action Research principles and Foucault's concepts of power, discourse and resistance to develop a change process that deconstructs the power relations that currently exclude marginalised rural health consumers from mainstream health services. It sets up processes for continuous learning and consumer responsiveness. Results: The approach proposed could provide a Continuous Quality Improvement process for creating more inclusive mainstream health institutions and fostering better engagement with many marginalised groups in rural communities to improve their access to health care. Conclusion: The approach to improving cultural inclusion in mainstream rural health services presented in this article builds on existing initiatives. This approach focuses on engaging on‐the‐ground staff in the need for change and preparing the service for genuine community consultation and responsive change. It is currently being trialled and evaluated.